Culture and power : a history of cultural studies - Gibson, Mark. (Sydney : UNSW Press, 2007)
"Power has long been a central preoccupation of social and cultural analysis. Culture and Power focuses on power to shape a history of Cultural Studies. A critical analysis of the nature and purpose of Cultural Studies, the book assesses the development of the discipline from the work of Michel Foucault in post-war France and the Birmingham Centre for Cultural Studies in the 1970s to the expansion of the field in the United States and present-day concerns with culture, politics and ethics." "As Cultural Studies has shifted, the concept of power has changed and become more problematic. Moving on from the celebrated 'culture wars' - and battles over language, objective knowledge and disciplinary values and meanings - Culture and Power unravels the social, ideological and political knots bound up in the concept of power. In doing so, the book charts not only the history but also the possible future of Cultural Studies."--BOOK JACKET.
Cultural studies and the concept of power -- With respect to Foucault: towards a critique of the thematics of power -- Power and the state: the peculiarities of the English revisited -- Cultural studies "before power": the first generation -- "A whole way of conflict": the turn to power -- The sociological encounter: "power" at Birmingham -- A continuing tension: the unresolved politics of cultural studies -- "An impossible politics to live": gender, race and the calculus of oppression -- The trans-Atlantic passage: "power" in America -- The shoals of banality: living with the concept of power -- Beyond power? The "new pluralism" and the turn to ethics -- Orientalism and occidentalism: "power" in international cultural studies -- Conclusion: reconfiguring cultural studies.
Includes index.
Bibliography: p. 207-219.
Keywords: Culture -- Study and teaching; Power (Social sciences); Cultural studies (Australia); History